Efficacy Of Clerodendrum Inerme L. (Garden Quinine) Against Some Human Pathogenic Strains - JASVINDER KAUR CHAHAL; RENU SARIN; MANVI MALWAL (International Journal of Pharma and Bio Sciences, 2010)
The present investigation was undertaken to evaluate in vitro antimicrobial activities of different extracts (ethanol, benzene and aqueous) of Clerodendrum inerme plant parts. In vitro antimicrobial efficacy of various extracts of C. inerme was assessed by disc diffusion method against Gram positive - Bacillus subtilis (ATCC 6633), Staphylococcus aureus (ATCC 25923) Gram negative- Escherichia coli (ATCC 25922), Psedomaonas aeruginosa (ATCC 27853) and fungal strains Aspergillus niger (ATCC 16404), Aspergillus flavus (ATCC 9807), Candida albicans (ATCC5027) and Candida glabrata (ATCC 66032). The methanol leaves extract exhibited highest zone of inhibition against S. aureus and A. niger (16.67 ±0.47 and 15.0±0.0 mm, respectively) with low MIC values (0.78 mg/ml for each). However, none of activity is shown by aqueous extract against tested pathogenic strains. Results of the present investigation indicate that Clerodendrum inerme possess compounds with antimicrobial properties and hence can be exploited for future natural plant based antimicrobial agents.